Protective effect of apoptosis signal-regulating kinase1 inhibitor against mice liver injury - Ping He Bo Zeng Xiao-Li Zhang Dian-Liang Fang Xia-Qia Zhou Ke-Qiang Wan Wen-Guang Tian (亚太热带医药杂志（英文版）, 2016)
Objective:To explore the protective effect and its molecular mechanism of apoptosis signalregulating kinase 1(ASK1) inhibitor(GS-459679) on acetaminophen-induced liver injury in mice.Methods:The model of liver injury was established by administration of acetaminophen(APAP)(300 mg/kg,i.p.) on C57BL/6 mice.Forty-eight male C57BL/6 mice were randomly divided into four groups,consisting of control group,GS group(GS-459679,30 mg/kg,i.p.),APAPinduced group,and GS combined with APAP-induced group.For GS combined with APAPinduced group,mice were treated with GS 30 min prior to administration of APAP.After mice were euthanized at 6 h or 12 h.respectively,serum levels of alanine aminotransferase(ALT) and aspartate aminotransferase(AST) were analyzed,and mRNA levels of TNF- α,IL-6 and IL-1βwere tested.The activity of glutathione(GSH),oxidized GSH(GSSG) and malondialdehyde were quantified.In addition,ASK1,P-ASK1,JNK and P-JNK protein levels were tested in all groups.Results:The ASK1 and P-ASK1 levels were up-regulated in APAP-induced group.Compared to the control group,serum levels of ALT and AST.and mRNA levels of TNF- a,IL-6 and IL-1(3were increased in APAP-induced group.Meanwhile,the levels of MAD and GSSG.and the ratio of GSSG/GSH were higher and the JNK was activatedin APAP-induced group compared with that in control group.However,compared to APAP-induced group,GS combined with APAP-induced group displayed a decrease of protein expression levels of ASK 1,P-ASKI and P-JNK,a reduction of serum levels of ALT and AST,a decrease in TNF- a.IL-6 and IL-1(3 mRNA levels,and a low ration of GSSG/GSH.Conclusions:GS-459679 treatment effectively down-regulates ASK1 and P-ASK 1 expression.Addition of GS-459679 decreases the generation of liver metabolites and inflammatory factors,reduces oxidative stress reaction,inhibits JNK activation,and then protects the responsiveness to APAP-induced liver injury.